Model Konsep Kurikulum Sebagai Dasar Pengembangan Kurikulum - Devi Fatwanti; Yudiestiera Arie Septian; Siti Fatimah Safitri; Umi Hani; Rofiqoh Syifa Aulia (AZKIA: Journal of Islamic Education in Asia, 2026)
This study aims: (1) To understand the concept of curriculum models as the basis for curriculum development, (2) to identify four concept models of curriculum formulated by education experts, namely academic subject models, humanistic, social reconstruction, and technological, and (3) to analyze the role of these models as the foundation for developing a contextual and future-oriented curriculum in Indonesia. This study uses a qualitative method with a descriptive- analytical approach through literature studies. Data sources are taken from classic textbooks such as the work of John D. McNeil, the latest scientific journals (2024–2025), and official documents for national curriculum development. Data analysis techniques are carried out by interactive data collection, reduction, data presentation, and drawing conclusions. The results of the study show that: (1) The concept model of curriculum is a theoretical framework that integrates philosophy, psychology, sociology, and juridical as a systematic basis for curriculum development; (2) The four models have complementary characteristics the academic subject model focuses on mastering disciplinary knowledge, the humanistic on developing individual potential, the social reconstruction on solving societal problems, and the technological on integrating digital technology; (3) These models form the basis for developing adaptive curricula, such as the Independent Curriculum, to produce competitive graduates in the Society 5.0 era.